(untitled) (Italian Journal of Public Health, 2005)
Switzerland showed its commitment to innovation in health care since the early 80th , implementing agencies and government units with the mission to promote and to appropriately govern innovation. The Swiss Network of Technology Assessment (SNHTA) was founded in 1998. The aim is the promotion and implementation of Health Technology Assessment projects in Switzerland by providing a neutral forum for the identification and the pursuit of common interests. This includes the coordination, exchange and dissemination of experiences of HTA projects and the implementation of the results. The collaboration in international projects is a priority. Ultimately SNHTA has the goal to improve efficacy, cost effectiveness and social accountability. An inventory survey amongst the members confirmed a high level of diverse specialised competencies, mainly employed within the institution. Only 20% of the HTA specific competencies are used for external activities. The need for integration of all partners in the field of innovation in a network has been recognised by the Swiss government. This lead to the creation of a webplatform in which all players involved in the business of medical technologies are involved. This platform (swiss medtech), includes patients, insurers, industry, universities and professional organisations. The joined activities include agreements on intellectual property and the integrated patient care chain. New ways to connect players in innovation are needed to face the challenge of increasing costs and diminishing resources.